A Practical Comparison of Waqf (Islamic Endowment) in Indonesia and Other Countries - Sulistiawati, Nila; Rini, Rini; Nadratuzzaman, Muh.; Amalia, Euis (Jurnal Indonesia Sosial Sains, 2023)
The definition of waqf in one of the results of this study is "Waqf functions to realize the potential and economic benefits of waqf assets for the benefit of worship and promote public welfare". In several discussions related to waqf, it is known that Indonesia as a country with the largest Muslim population in the world has very good waqf potential. One of the research articles it is known that: The research results describe a high level of awareness about cash waqf among millennials in Indonesia. The results further reveal a lower level of willingness to contribute to cash waqf in the sample population than their level of awareness about cash waqf. In general, challenges that can be managed better for increasing waqf include several things, namely; lack of socialization. In general, the community does not understand waqf law properly and correctly, both in terms of the pillars and conditions of waqf, as well as the legal intent of waqf, Management and Management, Waqf Objects and Nadzir Commitments, and the weakness of the control system. Waqf opportunities can still be developed in accordance with existing research results; Indonesia needs to encourage the practice of waqf experts and musytarok (such as CWLS) so that waqf practice in Indonesia is more dynamic; The method of expert waqf can be reserved for the rich as part of wealth management; The practice of musytarok waqf can be intended to help the poor to be able to meet their primary needs, such as housing, hospitals, etc